Importance of the Ni/W ratio in NiW/Alumina catalysts for hydrotreating of model compounds and low temperature coal tar - Zhang, H.; Zhang, Shu; Zhang, P.; Wang, Y.; Xu, D. (2012)
Low temperature coal tar is a potentially abundant feedstock for the oil refineries and can be catalytically hydrotreated to obtain jet fuel. Alumina supported Ni-W catalysts with different Ni/W atom ratios were prepared and characterized by BET, SEM, XRD and H 2 -TPR. Their catalytic activities were investigated on a trickle bed reactor by hydrotreating cresol-naphthalene model compounds in n-heptane solution. The results show that all the catalysts had excellent hydrodeoxygenation and hydrogenation activities while the promotion of Ni on WS 2 exhibited a plateau for naphthalene hydrogenation. The most active catalyst was selected for hydroprocessing a low temperature coal tar fraction; the product and the kerosene fraction were analyzed by GC-MS and elementary analyser. Phenols and di-aromatics in the tar were almost converted while percentages of cycloalkanes and hydro-aromatics increased significantly. In the meantime, heteroatoms, especially O atoms, reduced remarkably.